2021
DOI: 10.1128/msphere.00011-21
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics and Evolution of SARS-CoV-2 Demonstrate the Necessity of Ongoing Viral Genome Sequencing in Ontario, Canada

Abstract: Genome-wide variation in SARS-CoV-2 reveals evolution and transmission dynamics which are critical considerations for disease control and prevention decisions. Here, we review estimates of the genome-wide viral mutation rates, summarize current COVID-19 case load in the province of Ontario, Canada (5 January 2021), and analyze published SARS-CoV-2 genomes from Ontario (collected prior to 24 November 2020) to test for more infectious genetic variants or lineages. The reported mutation rate (∼10−6 nucleotide [nt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…While higher than other predictions 4 , this frequency is comparable to similar observations in poliovirus, which also utilizes an RdRp for replication but lacks an associated proofreading activity 8,11,26 . The error frequency estimations were previously based on the presence of a proofreading 3'-to-5' exoribonuclease (ExoN, nsp14) in SARS-CoV-2 that is distinct from the viral RdRp 27 . The same proofreading activity has been implicated in promoting template switching 28 , which we show here is error-prone.…”
Section: Discussionmentioning
confidence: 99%
“…While higher than other predictions 4 , this frequency is comparable to similar observations in poliovirus, which also utilizes an RdRp for replication but lacks an associated proofreading activity 8,11,26 . The error frequency estimations were previously based on the presence of a proofreading 3'-to-5' exoribonuclease (ExoN, nsp14) in SARS-CoV-2 that is distinct from the viral RdRp 27 . The same proofreading activity has been implicated in promoting template switching 28 , which we show here is error-prone.…”
Section: Discussionmentioning
confidence: 99%
“…Data for 24,244 complete (>29,000 base pairs), high coverage (<1% N’s), and nonduplicate SARS-CoV-2 genomic sequences in FASTA format sampled from January 1, 2020, to December 31, 2021, were retrieved from the GISAID database on January 1, 2022 [ 20 ]. Metadata associated with each genomic sequence, including sampling date and GISAID clade assignment [ 37 ], were also retrieved from the GISAID database.…”
Section: Methodsmentioning
confidence: 99%
“…Previous SARS-CoV-2 genomic studies have characterized the landscape of mutation types and allele frequencies around the world, including but not limited to the United States [ 14 ], Qatar [ 15 ], the United Kingdom [ 16 ], Uruguay [ 17 ], and Canada [ 18 ]. Public health policies implemented in different countries to reduce COVID-19 transmission may in part influence the emergence of novel SARS-CoV-2 genetic variants [ 19 ] and mutation rates that can lead to the evolution of resistance to vaccines [ 20 ]. For instance, genomic epidemiology of the first 2 waves of SARS-CoV-2 in Canada revealed that the number of sublineages imported to Canada reduced by over 10-fold when restrictions of foreign nationals were implemented in March 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The good thing about the Mpox vaccination is we can easily achieve herd immunity. Since MPXV has a double-stranded DNA, its genomic material is more stable than RNA viruses (e.g., SARS-CoV-2 and influenza A virus), making the mutation rate slow; thus, making our vaccines effective against infection and achieving herd immunity (25). The second goal includes public health policy modifications, which will increase health communication and education funds on Mpox, availability of diagnostic tests and vaccines, and workforce for wider surveillance.…”
Section: Infection Prevention and Control Practices Against Mpoxmentioning
confidence: 99%